2015
DOI: 10.1007/s00894-015-2638-9
|View full text |Cite
|
Sign up to set email alerts
|

Microsolvation and hydration enthalpies of CaS2O3(H2O) n (n = 0–19) and S2O3 2−(H2O) n (n = 0–16): an ab initio study

Abstract: We studied microhydrated calcium thiosulfate and its ions at the restricted Hartree-Fock RHF/6-31G* level of theory. A semiempirical molecular dynamics search of progressively more hydrated species provided lowest-energy configurations that were then fully optimized and characterized as energy minima at the RHF/6-31G* level of theory. The first solvation shell of calcium thiosulfate contains 18 water molecules, while the first solvation shell of thiosulfate ion consists of 15 water molecules. QTAIM calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These simulations revealed that 8.9 water molecules were required to complete the first solvation shell of thiosulfate, and 3.5 water molecules were present around the terminal S atom. The ab initio study of S 2 O 3 2– (H 2 O) n ( n = 0–16) clusters highlighted the presence of 15 water molecules in the first solvation shell of thiosulfate. However, the ultrasonic velocity data of an aqueous solution of thiosulfate predicted the appearance of 13 water molecules in the first solvation shell of the thiosulfate ion .…”
Section: Introductionmentioning
confidence: 99%
“…These simulations revealed that 8.9 water molecules were required to complete the first solvation shell of thiosulfate, and 3.5 water molecules were present around the terminal S atom. The ab initio study of S 2 O 3 2– (H 2 O) n ( n = 0–16) clusters highlighted the presence of 15 water molecules in the first solvation shell of thiosulfate. However, the ultrasonic velocity data of an aqueous solution of thiosulfate predicted the appearance of 13 water molecules in the first solvation shell of the thiosulfate ion .…”
Section: Introductionmentioning
confidence: 99%